Visible nations : Latin American cinema and video - Noriega, Chon A., 1961- (University of Minnesota Press, 2000)
In the current "global" moment, the study of Latin American cinema has become insistently nationala phenomenon fully explored in this collection of essays by some of the most interesting and innovative scholars of media and Latin American culture working today.